ASSESSMENT OF THE NATIONAL WEALTH OF UKRAINE AND ANALYSIS OF ITS GROWTH FACTORS (Economic journal of Lesya Ukrainka Volyn National University, 2020)
The study of the category of National Wealth is necessary because the wealth of the nation is an important indicator of the economic power and potential of the country. In this regard, the study of national wealth has become particularly popular in recent years in countries with transformational economies, where the absence of market relations over a long time has led to an unbiased valuation of property and their too low cost in privatization.Today, there are no similar views on the definition of the essence of National Wealth. The ambiguity of interpretations of the term «National Wealth» and his assessment methods may indicate a lack of scientific research in this field.The purpose of the work is to study the concept, structure, methods of assessment, and most importantly - ways to increase the national wealth of Ukraine. After all, determining the composition and state of national wealth of the country reveals the main priorities of development, namely: structural policy, privatization policy, investment policy, etc.The article highlights the modern understanding of the essence and meaning of the category "national wealth". The evolution of methodological approaches to assessing national wealth and defining its components are considered. The dynamics of national wealth were analyzed using the National Accounts System. The type of national economy over the last five years has been determined taking into account the dynamics of National Wealth and Gross Domestic Product. The necessity for inclusion to the national wealth the human capital was confirmed and justified. An attempt has been made to calculate human wealth according to the World Bank methodology and the statistical base of the State Statistics Service of Ukraine. A variance analysis of the components of national wealth has been carried out in order to assess its growth factors.The results of the analysis conclude that the priority direction for the growth of national wealth in Ukraine is investment in human capital.
Keywords: national wealth, produced capital, natural capital, human capital, analysis of variance